f(x) = 5 − 3x + 4x2
f(a + h)
Thank you for the opportunity to help you with your question!
f(a) = 5 − 3a + 4a^2
f(a+h) = 5 − 3(a+h) + 4(a+h)^2 = 5 − 3a-3h + 4a^2+4h^2+ 8ah
[f(a+h) - f(a)]/h = (5 − 3a-3h + 4a^2+4h^2+ 8ah - 5+ 3a-4a^2 ) /h
= (-3h + 4h^2 +8ah)/h = 4h+8a-3
please let me know if you have any problem in understanding the solution or need more clarification and details . i will be more happy to help youplease best me in review best of luck :)
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?